2018
DOI: 10.11591/ijpeds.v9.i1.pp180-188
|View full text |Cite
|
Sign up to set email alerts
|

Design, Control and Monitoring of an Offline Mobile Battery Energy Storage System for a Typical Malaysian Household Load Using PLC

Abstract: Battery energy storage system (BESS) is used in many practical applications including uninterruptible power supplies (UPS), portable devices, electrical vehicles and renewable energy systems. To utilize BESS effectively, an efficient control operation is required. Various controllers have been introduced in the open literature. However, they are not considered the best fit due to their limitations. This includes their incapability of handling high-power rating BESS, low noise immunity, short life cycle and lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In relation to the definitional objectives to be determined as part of the research, the discussions in relation to the results obtained are detailed. In the first place, it was found that under the control strategy proposed and implemented in the sand granulation process, it was possible to improve the percentage of humidity, which consequently will improve the homogeneity in the manufacture of ceramic tiles, this percentage improvement turned out to be 94.78%; In this regard, in the research carried out by [38], in which it specifies that through an automated system it manages to improve the quality of the sand granulation process by 55.75%, in this aspect it is from a point of view that it is a fact that industrial automation improves various aspects in a process, however, what is relevant and outstanding is to what extent the improvement is made, and in this aspect the strategy used is highly significant and contributes much to improving the quality of the manufacturing process of ceramic tiles.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the definitional objectives to be determined as part of the research, the discussions in relation to the results obtained are detailed. In the first place, it was found that under the control strategy proposed and implemented in the sand granulation process, it was possible to improve the percentage of humidity, which consequently will improve the homogeneity in the manufacture of ceramic tiles, this percentage improvement turned out to be 94.78%; In this regard, in the research carried out by [38], in which it specifies that through an automated system it manages to improve the quality of the sand granulation process by 55.75%, in this aspect it is from a point of view that it is a fact that industrial automation improves various aspects in a process, however, what is relevant and outstanding is to what extent the improvement is made, and in this aspect the strategy used is highly significant and contributes much to improving the quality of the manufacturing process of ceramic tiles.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, automation is taken as a security control measure for jobs that are considered high risk, thereby protecting the integrity of the working personnel, minimizing the danger and reducing the risk of an accident. Authors in [38]- [43] are indicating that automation processes in industry 4.0 provide greater speed and productivity in food processes. Using three PLCs that communicate via Profibus using the Master-Slave protocol, greater efficiency has been achieved in the filling, dosing, packaging and transport processes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was also shown that GAC is a suitable support carrier for the cultivation of microorganisms in biogas production. Biofilms formed on the surface of GAC were stable, and they provided an environment that was rich in nutrients that favored the microbes [28]. When fitted into the modified Gompertz equation, it was found that the highest biogas production A = 934.54 mL/gVS, maximum biogas production rate U = 60.55 mL/gVS.day, and lastly lag phase λ =1.04 days.…”
Section: Microbial Kinetic Studiesmentioning
confidence: 99%